Penentuan Batas DAS Tojo Berbasis GIS Menggunakan Perangkat HEC HMS 4.4 dan QGIS 3.16 - Aswar Amiruddin; Asta Asta; Rosmalia Handayani (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
Watershed delineation is the process of determining an area that contributes to the flow of rainfall (precipitation) into runoff to the outlet. The watershed delineation analysis in this study used the HEC-HMS version 4.4 and QGIS 3.16 . HEC HMS version 4.4 has GIS tools that have been directly integrated to facilitate the watershed delineation process. The study area in this research is the Tojo watershed which is located in Central Sulawesi Province. The digital elevation model (DEM) data source used is DEMNAS BIG with a spatial resolution is 8,1 meters. The results of watershed delineation using HEC-HMS 4.4 software are the same as the results of watershed delineation using QGIS 3.16 software. There is a slight difference in the watershed boundary in some parts when zoomed in. The watershed area produced by each GIS Softwares are HEC-HMS 212,583 km2, QGIS 212,5404 km2. The HEC-HMS 4.4 software gives quite good results on the boundary analysis of the Tojo watershed, so the HEC-HMS 4.4 software can also be used in other researches in the field of water resources.